2021
DOI: 10.3390/cancers13163998
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches in Characterization of Lesions Dissemination in DLBCL Patients on Baseline PET/CT

Abstract: Dissemination, expressed recently by the largest Euclidian distance between lymphoma sites (SDmax), appeared a promising risk factor in DLBCL patients. We investigated alternative distance metrics to characterize the robustness of the dissemination information. In 290 patients from the REMARC trial (NCT01122472), the Euclidean (Euc), Manhattan (Man), and Tchebychev (Tch) distances between the furthest lesions, firstly based on the centroid of each lesion and then directly from the two most distant tumor voxels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…20 Disease dissemination markers appear to be more promising biomarkers that are independent from tMTV and provide information beyond that afforded by imaging stage (Figure 1). This was first reported in patients with DLBCL by Cottereau et al 21,22,55 The simplest of the measurements reported was the largest distance between the center of two lesions in the body (Dmax) adjusted for body surface area (SDmax) but others such as the distance between the bulkiest lesion and the lesion furthest away (Dmaxbulk) as well as measurements of lesional spread, whereby distance between lesions are summed were also prognostic 21 (Figure 1). In HL, Dmax was reported to be an independent predictor of PFS from baseline tMTV and clinical risk factors, adjusted for radiotherapy and treatment intensification 53 including the subgroup who achieved early complete metabolic response (CMR).…”
Section: Recently a Model Was Developed Incorporating Baseline Mtv4mentioning
confidence: 82%
“…20 Disease dissemination markers appear to be more promising biomarkers that are independent from tMTV and provide information beyond that afforded by imaging stage (Figure 1). This was first reported in patients with DLBCL by Cottereau et al 21,22,55 The simplest of the measurements reported was the largest distance between the center of two lesions in the body (Dmax) adjusted for body surface area (SDmax) but others such as the distance between the bulkiest lesion and the lesion furthest away (Dmaxbulk) as well as measurements of lesional spread, whereby distance between lesions are summed were also prognostic 21 (Figure 1). In HL, Dmax was reported to be an independent predictor of PFS from baseline tMTV and clinical risk factors, adjusted for radiotherapy and treatment intensification 53 including the subgroup who achieved early complete metabolic response (CMR).…”
Section: Recently a Model Was Developed Incorporating Baseline Mtv4mentioning
confidence: 82%
“…Interestingly, the cut-off values to characterize the lesion dissemination (Dmax and sDmax) in DLBCL patients on baseline PET images were almost identical on the independent cohorts. Dmax and sDmax were defined empirically, yet a recent study has shown that the distance between lesions calculated using different distance measurement methods (namely Euclidean, Manhattan, and Chebyshev) in 3D yielded similar results in predictions of the outcome (21).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the inclusion and exclusion criteria mentioned above, 312 records were excluded (96 as not in the field of interest; 48 as reviews, editorials, or letters; 141 as case reports or case series; and 27 as conference abstracts). Eighteen remaining records were eligible for inclusion in the systematic review (qualitative synthesis) after a full-text assessment [10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. No additional records were assessed as suitable for inclusion after screening the references of these articles.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…assessment [10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. No additional records were assessed as suitable for inclusion after screening the references of these articles.…”
Section: Of 11mentioning
confidence: 99%